2009
DOI: 10.1348/096317908x325313
|View full text |Cite
|
Sign up to set email alerts
|

Safety leadership: A longitudinal study of the effects of transformational leadership on safety outcomes

Abstract: Transformational leadership based interventions were assessed using a pre‐test, post‐test, and control group design. Leaders (N=54) from 21 long‐term health care organizations were randomly assigned to general transformational leadership training, safety‐specific transformational leadership training, or a control group. Multivariate analysis of variance (MANOVA) showed that leadership training resulted in significant effects on manager post‐training ratings of safety attitudes, intent to promote safety, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
230
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(246 citation statements)
references
References 48 publications
9
230
0
7
Order By: Relevance
“…Leader characteristics and behaviors work to reduce hospital errors through enabling and shaping perceptions of safety climate. Transformational leadership-providing an inspiring vision and fostering identification with it-is the leader characteristic most strongly associated with improving safety culture and safety outcomes (92), and transformational leadership can also be taught (96).…”
Section: Internal Motivatorsmentioning
confidence: 99%
“…Leader characteristics and behaviors work to reduce hospital errors through enabling and shaping perceptions of safety climate. Transformational leadership-providing an inspiring vision and fostering identification with it-is the leader characteristic most strongly associated with improving safety culture and safety outcomes (92), and transformational leadership can also be taught (96).…”
Section: Internal Motivatorsmentioning
confidence: 99%
“…Another research found that a transformational CEO motivates and inspires others to excel towards both organisational and individual excellence (Zhu et al 2005). In the healthcare industry, safety-specific transformational leadership training is considered as a low cost intervention that has positive effects on a variety of safety outcomes including safety climate (Mullen and Kelloway 2009). …”
Section: Transformational Leadershipmentioning
confidence: 99%
“…The markers of a transformational leader range from the articulation of strongly-held beliefs to an overall commitment to the organisation (Bass and Bass 2009). It was outlined by Mullen and Kelloway (2009) that there is a considerable lack of transformational based leadership interventions targeted towards safety within the leadership literature. This gap will be addressed through this research under the guise of defining safety leadership.…”
Section: Literature Review General Leadershipmentioning
confidence: 99%
“…Safety leadership within itself is a concept that borrows heavily from the leadership framework with specifics being based upon transformational leadership (Mullen and Kelloway, 2009). Throughout this research, safety leadership will be explored and defined with the main research question being framed as: How do leaders within the construction environment define safety leadership and how does safety leadership differ from other leadership disciplines?…”
Section: Introductionmentioning
confidence: 99%